ELECTROCHEMICAL CORROSION PERFORMANCE OF COMMERCIALLY USED ALUMINIUM ENGINE BLOCK AND PISTON IN 0.1M NaCl (Journal of Mechanical Engineering, 2015)
The corrosion behaviour of commercially used aluminium engine block and piston were investigated in 0.1M NaCl solution at room temperatures. The study was done by electrochemical method, using Tafel polarization and electrochemical impedance spectroscopy (EIS) techniques. The surface was characterized by optical microscope and scanning electron microscope (SEM). The results indicated differences in the charge transfer resistance of engine block and piston alloys. The current density (Icorr) of engine block material showed higher value than that of piston material. The corrosion potential (Ecorr) and pitting corrosion potential (Epit) of piston material were shifted to the more noble direction. In aluminium piston alloy there seems to be uniform surface pits formations which are in fewer amounts as compared to those in engine block alloy. The corrosion performance of aluminium piston alloy was found to be higher than that of aluminium engine block due to the presence of Ni and lower percentage of Fe in aluminium piston alloy.